The role of perceived environment, neighbourhood characteristics, and attitudes in walking behaviour: evidence from a rapidly developing city in China - Chan, E; Schwanen, T; Banister, D (Springer, 2019)
The associations between objective and subjective dimensions of the built environment and walking behaviour have been examined extensively in existing studies. However, the interaction effects of those dimensions of the built environment on walking behaviour are understudied and may be more complex than hitherto suggested. Apart from the subjective dimensions of the built environment, walking attitudes also play a role in moderating these relationships. This paper investigates the independent and joint effects of objective neighbourhood characteristics, people’s perceptions of the neighbourhood environment, and walking attitudes on the frequency of walking by using Shenzhen as a case study. Since those effects may vary across different kinds of walking trips, the analysis looks separately at three major types of walking at the neighbourhood level—walking for work/school, walking for leisure/recreation, and walking for household responsibilities. Logistic regression analyses confirm that the correlates of people’s walking frequency vary considerably among different types of walking. Statistically significant interaction effects of objective neighbourhood characteristics and perceived environment are found. The results suggest that positive perceptions of the environment can compensate for the effect that low objective walkability of neighbourhoods has on people’s walking frequency. When seeking to encouraging walking at the neighbourhood level, policymakers should not only concentrate on improving objective neighbourhood characteristics but also consider people’s perception of the neighbourhood environment and their attitudes towards walking.